The Mystical Soundscape and The Functions of Commentaries on Ibn AL-FĀRIḌ’S (d. 632/1235) NAẒM AL-SULŪK - Aboulwafa, Sherine Mohsen (AUC Knowledge Fountain, 2026)
This thesis examines Ibn al-Fāriḍ’s Naẓm al-Sulūk and its earliest commentaries by al-Farghānī (d. 700/1300) and al-Tilimsānī (d. 690/1291) through the analytical framework of the mystical soundscape. Rather than treating the poem and its commentaries as static texts, it argues that meaning in this corpus emerges as an experiential and perceptual event sustained through sound, silence, and reception. The mystical soundscape is conceptualized as comprising two interrelated domains: a silent soundscape, formed through reading, memory, imagination, and conceptual engagement; and an audible soundscape, formed through recitation, pronunciation, rhythm, and communal audition. These domains are linked by the experience of bewilderment (ḥayra) as a central apophatic mode of knowing. Chapter One reads Naẓm al-Sulūk as a silent mystical soundscape, showing how its poetic lexicon, structure, and sonic ambiguity enact apophatic experience rather than merely describing it. Chapter Two analyzes al-Farghānī’s commentary as a conceptual extension of this soundscape, in which poetic ambiguity is preserved through apophatic exposition. Chapter Three examines al-Tilimsānī’s commentary as a sonic intervention that regulates pronunciation and audition, mediating the poem’s reception within communal and performative contexts. Together, these layers reconceive Naẓm al-Sulūk and its commentaries as a dynamic mystical soundscape in which meaning remains active, contested, and continually re- experienced. By foregrounding soundscape as a methodological orientation, the thesis contributes to studies of Sufi poetry, commentary, and reception history by challenging rigid binaries between text and orality, doctrine and experience.